Things that make for peace: traversing text and tradition in Christianity and Islam - Rees, Anthony (Lexington Books, 2020)
First things / Anthony Rees -- Peace, nonviolence, and Islam / Zeki Saritoprak -- Like lightning? : Luke 17:22-37 revisited in interfaith perspective / David J. Neville -- The prophets as archetypes of peace in the Qur'an : the use and nonuse of Isrā ʼīliyyāt sources in the story of Mūsa / Mahsheed Ansari and Hakan Coruh -- From cultures of violence to ways of peace : reading the Benedictus in the context of Australia's treatment of asylum seekers in offshore detention / Anne Elvey -- A prophetic stance against violence : analysis of the Meccan period of prophet Muhammad's life and the centrality of peace as a preferred method / Suleyman Sertkaya -- Leaving judgment to God : Jonah's struggle / Marie-Louise Craig -- An apocalypse that welcomes others? Reading Revelation peacefully / U-Wen Low.